Characterization of the burning velocity of hydrogen/methane blends in a constant volume combustion bomb - Reyes, M.; Tinaut, F. V. (2017 8th International Conference on Mechanical and Aerospace Engineering (ICMAE), 2017)
In the present work a study of the burning velocity of hydrogen and mixtures of methane and hydrogen in different proportions obtained in a constant volume combustion bomb is presented. Hydrogen is an important energy carrier that contributes to the energy diversification and can be produced from different fossil and renewable energy sources. This work describes a method to determine laminar burning velocity based on the use of a spherical constant volume combustion bomb and a two-zone combustion analysis model. The main interest of using a constant volume combustion bomb is the possibility of reaching high values of thermal conditions of pressure and temperature, engine-like conditions. Experimental pressure is analyzed by means of a combustion model to obtain the burning velocity and other properties. Correlations for the burning velocity are presented as power laws of pressure and temperature and are compared with other authors' results showing a good agreement.